2021
DOI: 10.18632/aging.202661
|View full text |Cite
|
Sign up to set email alerts
|

Linc00641 promotes the progression of gastric carcinoma by modulating the miR-429/Notch-1 axis

Abstract: Linc00641 plays different roles in various types of human cancers. However, the function of linc00641 and its underlying mechanism of action in gastric cancer have not been fully elucidated. Therefore, the aim of our current study was to explore the molecular mechanism of linc00641 in gastric cancer. MTT assays, flow cytometry, wound healing assays, and Transwell invasion assays were utilized to measure cell viability, apoptosis, migration and invasion, respectively. Western blotting and RT-PCR assays were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We identified 144 key m6A-related lncRNAs, nine of which were included in the MLPS. LINC00641 was reported to be an oncogene in acute myeloid leukaemia ( 26 ), colorectal carcinoma ( 27 ) and gastric carcinoma ( 28 ). Conversely, LINC00641 has been studied and reported as a tumor inhibitor in many cancers, including prostate cancer ( 29 ), bladder cancer ( 30 ), renal cancer ( 31 ), cervical cancer ( 32 ), non-small-cell lung cancer ( 33 ) and breast cancer ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…We identified 144 key m6A-related lncRNAs, nine of which were included in the MLPS. LINC00641 was reported to be an oncogene in acute myeloid leukaemia ( 26 ), colorectal carcinoma ( 27 ) and gastric carcinoma ( 28 ). Conversely, LINC00641 has been studied and reported as a tumor inhibitor in many cancers, including prostate cancer ( 29 ), bladder cancer ( 30 ), renal cancer ( 31 ), cervical cancer ( 32 ), non-small-cell lung cancer ( 33 ) and breast cancer ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…LINC00641 and miR-582-5p participate in the regulation of oxaliplatin resistance by altering autophagy in gastric adenocarcinoma, providing a direction for the treatment of gastric cancer. Hang et al ( 38 ) also found that silencing LINC00641 in gastric cancer cell line reduced the proliferation, migration and invasion of cancer cells and induced apoptosis. After down regulating LINC00641 in cells, the expression of miR-429 increased.…”
Section: Role Of Linc00641 In Cancermentioning
confidence: 97%
“…Liu ( 36 ) analyzed 23 prostate cancer patients and found that the low LINC00641 expression group had a lower survival rate than the high LINC00641 expression group (P < 0.05). Hu ( 38 ) detected the expression of LINC00641 in 173 cases of gastric cancer, which was related to M stage (P < 0.01). Cox regression model including LINC00641, miR-582-5p, CEA and age could predict the 1-year and 3-year survival rates of gastric cancer patients (C index was 0.876 ± 0.06).…”
Section: Clinical Significance Of Linc00641mentioning
confidence: 98%
See 2 more Smart Citations